2014
DOI: 10.1515/ijdhd-2014-0339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a subject on leadership and intrapersonal development: views of the students based on qualitative evaluation

Abstract: Tomorrow's Leaders" is a subject developed to satisfy the leadership and intrapersonal development requirement at The Hong Kong Polytechnic University. After taking this subject, students were invited to use three descriptors and a metaphor to describe their experiences about the subject. Based on the reflections of 143 students, results showed that 94.4% of the descriptors used by informants were positive and 2.31% of the descriptors were negative. For the metaphors used to describe the subject, 92.7% were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Students reported, for instance, that teachers were not only well-prepared for the lecture material, but also motivating, caring for, and respecting their students during class. This was also consistent with the findings of three other studies that analyzed teachers' reflections on the preparation and delivery of this lecture (Shek et al, 2022d(Shek et al, , 2023a. We analyzed the views of six, eight and nine teachers after Semesters 1 and 2 of the 2021/22 academic year (hybrid mode) and Semester 1 of the 2022/23 academic year (face-to-face mode), respectively.…”
Section: Negative Responses (11 Responses)supporting
confidence: 85%
See 1 more Smart Citation
“…Students reported, for instance, that teachers were not only well-prepared for the lecture material, but also motivating, caring for, and respecting their students during class. This was also consistent with the findings of three other studies that analyzed teachers' reflections on the preparation and delivery of this lecture (Shek et al, 2022d(Shek et al, , 2023a. We analyzed the views of six, eight and nine teachers after Semesters 1 and 2 of the 2021/22 academic year (hybrid mode) and Semester 1 of the 2022/23 academic year (face-to-face mode), respectively.…”
Section: Negative Responses (11 Responses)supporting
confidence: 85%
“…These findings echoed the afore-mentioned positive quantitative results. Reflections of teachers teaching "Law-abiding Leadership" are consistent with students' perceptions, suggesting the beneficial lecture impacts on students are acknowledged by both students and lecturers (Shek et al, 2022d(Shek et al, , 2023a.…”
Section: Law Abidance Leadership Education In Hong Kongmentioning
confidence: 58%
“…Moreover, students finally are able to recognize and enjoy the benefits of inspirational teaching and learning pedagogy in most general education subjects, despite difficulties they encountered at the beginning. This assertion is evident by previous findings on how students perceived the general education subjects in Hong Kong -although some students expressed that they felt difficulty in digesting multidisciplinary knowledge and fulfilling educational demands in general education subjects, most students regarded the rich content and active pedagogy in these subjects as helpful and effective in cultivating their all-round competencies (Shek and Law 2014;Shek et al 2014b). As a result, students' achievement in different dimensions of learning outcomes found in the present study provides evidence for the value of the general education-embeded higher education system, which in general could help promote university students' holistic development.…”
Section: Discussionmentioning
confidence: 84%
“…For example, students' reflective essays showed their perceived improvement in different areas, such as intrapersonal and interpersonal qualities, ethical decision-making capacity, and effective leadership skills (Shek, 2013;Shek & Leung, 2014). Another qualitative study that asked students to use descriptors (e.g., fun, inspiring, useful) and metaphors (e.g., a mirror, an adventure, an interesting book) to describe the course also revealed that students responded positively to the course (Shek & Law, 2014). Nonetheless, these studies based on qualitative methodologies cannot offer students' evaluation of the multidimensional learning processes and learning outcomes of the course in a standardized format.…”
Section: Subjective Outcome Evaluationmentioning
confidence: 98%